Breaches of fundamental rights in African states by state agencies during covid-19: an overview (2020)
Coronavirus (COVID -19) is a global pandemic that affects the respiratory system, hinders easy breathing, may lead to death, and spreads cross-geographically through drops caused by an infected person’s cough, sneeze, or spit. Consequently, it is key for individuals to have free access to the enjoyment of their fundamental human rights at all times. Also, States strive to protect human rights without acting in breach in spite of the pandemic. However, Covid-I9 has justified constraints on the enjoyment of fundamental rights, especially, the» rights to life and health as attempts are made to restrict its transmission via the implementation of quarantine or isolation laws in various jurisdictions. In curbing its spread, many countries, particularly, African states, through the instrumentalities of state agencies, deny people of their rights in so many ways. Hence, this article examines significant International, Regional, and Local Human Rights Instruments on selected five African states; and their applicable Quarantine Laws; their practical responses to Covid-19; breaches committed; and recommends how states can respect human rights during pandemic period experienced in the year 2020.